2019
DOI: 10.3390/ijerph16152788
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Theory of Planned Behavior in Environmental Science: A Comprehensive Bibliometric Analysis

Abstract: Since the theory of planned behavior (TPB) was proposed by Ajzen in 1985, it has attracted extensive interest and been widely applied worldwide. Although an increasing number of studies have employed the TPB in the domain of environmental science, there have been no attempts to retrospectively analyze existing articles. The current study aimed to holistically understand the application status of the TPB in environmental science from a knowledge domain visualization perspective. A total of 531 journal articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 114 publications
(148 reference statements)
2
63
0
2
Order By: Relevance
“…Additionally, all keywords (including author keywords and keyword plus) extracted from a large number of pieces of literature by CiteSpace software were conducted to content analysis (Si et al 2019). There were two main steps employed in the content analysis of keywords to provide critical reviews.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Additionally, all keywords (including author keywords and keyword plus) extracted from a large number of pieces of literature by CiteSpace software were conducted to content analysis (Si et al 2019). There were two main steps employed in the content analysis of keywords to provide critical reviews.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Despite some criticism and several competing behavioral models, the TPB model is still regarded as the most effective model for designing behavioral interventions ( Yuriev et al., 2020 ). Therefore, researchers have been increasingly employing the TPB model across various disciplines including environmental science and sustainability management ( Daddi et al., 2018 ; Si et al., 2019 ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…However, especially in the field of environmental science, TPB is increasingly being advocated as a key theory for predicting and promoting a variety of Pro-Environmental Behaviors [22]. According to the study in [35] the primary research topics where TPB is applied are: waste management, green consumption, climate and environment, saving and conservation, and sustainable transportation. Previous literature dealing with TPB in the environment discourse has demonstrated that Attitudes, Subjective Norms, and Perceived Behavioral Control play key roles in shaping the Intention to engage in Pro-Environmental Behaviors [9] and such mechanisms can be further reinforced by people's moral obligation to perform PEB [36].…”
Section: Hypothesis Ontheory Of Planned Behavior and People's Responsmentioning
confidence: 99%